Подкурганные погребения восточноевропейских степей и пути сложения культуры Хазарии - Флёрова, В.Е. (Степи Европы в эпоху средневековья, 2001)
The paper gives a survey of the sources and hypotheses on tumulus interments of the Vllth - early IXth c.c. scattered over the area from the Dnieper to the Volga rivers. These monuments play an important role in investigating the ways of Khazaria’s culture formation. The author notes that in modem Ukrainian and Russian historiography there is a marked difference of opinion as to the ethnic, cultural and chronological attribution of these monuments. The following hypotheses could be mentioned: those attributing them mainly to the Khazars (Ye. Kruglov, A. Komar), or to the Bulgarians (Bagautdinov - Bogachev - Zubov, Matveyeva), and those indicating certain influence of the late Sarmat substratum (Vasyutkin, Maksimov). There are also considerable contradictions in chronological organisation of the material. In different authors divergence in dating various monuments can range from 50 to 100 years and more. Absolute dating being a complex problem, one cannot rely on the hypotheses based on chronological correlations with concrete historical events. Underdeveloped chronology makes it almost impossible to determine discreteness and continuity of such monuments as Sivashevka, Malaya Pereschepina, Voznesenka, “barrows with rectangular ditches”. Novinki and Urcn.